Advanced endoscopic techniques in the assessment of inflammatory bowel disease: new technology, new era. Issue 3 (22nd December 2018) - Iacucci, Marietta; Furfaro, Federica; Matsumoto, Takayuki; Uraoka, Toshio; Smith, Samuel; Ghosh, Subrata; Kiesslich, Ralf
Abstract : Endoscopic assessment of inflammation and mucosal healing is crucial for appropriate management in IBD. Current definition of endoscopic mucosal healing has been derived using previous generation of standard white light endoscopes. New endoscopy technologies widely available provide much more detailed images of mucosal and vascular patterns. Novel endoscopic techniques with high definition image, optical and digital enhancement have enhanced the quality and fine details of vascular and mucosal pattern so that endoscopic images have started to reflect histological changes for lesions and inflammation/healing. These technologies can now define subtle inflammatory changes and increase detection and characterisation of colonic lesions in patients with IBD. The best endoscopic technique to detect dysplasia in IBD is still debated. Dye chromoendoscopy with targeted biopsies is considered by Surveillance for Colorectal Endoscopic Neoplasia Detection and Management in inflammatory Bowel Disease Patients: International Consensus Recommendations (SCENIC consensus the standard of care and recommended for adoption by gastroenterologists in practice. In future, it is possible that well-trained colonoscopists using high definition equipment with image enhancements may be able to obtain equivalent yield without pan-colonic dye spraying and characterise lesions. Finally, SCENIC introduced endoscopic resectability of some dysplastic colonic lesions—new techniques may now better characterise endoscopic resectability and limit the number of colectomies. In this review, we will provide a state-of-the-art opinion on the direction of technological advances in the assessment of IBD and how new concepts will refine clinical practice.